Rethinking Opsins. (10th February 2022) - Feuda, Roberto; Menon, Anant K; Göpfert, Martin C
Abstract: Opsins, the protein moieties of animal visual photo-pigments, have emerged as moonlighting proteins with diverse, light-dependent and -independent physiological functions. This raises the need to revise some basic assumptions concerning opsin expression, structure, classification, and evolution.